2017
DOI: 10.1038/s41598-017-07299-1
|View full text |Cite
|
Sign up to set email alerts
|

Femtogram Level Sensitivity achieved by Surface Engineered Silica Nanoparticles in the Early Detection of HIV Infection

Abstract: We have engineered streptavidin labelled Europium doped fluorescent silica nanoparticles which significantly increased sensitivity without compromising the specificity of the immunoassay. As a proof of concept, a time resolved fluorescence based sandwich immunoassay was developed to detect HIV-1 p24 antigen in clinical specimens. The detection range of the silica nanoparticle based immunoassay (SNIA) was found to be between 0.02 to 500 pg/mL in a linear dose dependent manner. SNIA offers 1000 fold enhancement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 42 publications
0
19
0
1
Order By: Relevance
“…We diluted the healthy human serum 100 times, which in turn reduced the sample amount required for analysis [50]. We added three different amounts of NP antigen to the diluted serum to give the different final concentrations; the recovery values are shown in Table 2.…”
Section: Detection Of Np In Human Serummentioning
confidence: 99%
“…We diluted the healthy human serum 100 times, which in turn reduced the sample amount required for analysis [50]. We added three different amounts of NP antigen to the diluted serum to give the different final concentrations; the recovery values are shown in Table 2.…”
Section: Detection Of Np In Human Serummentioning
confidence: 99%
“…Thus, the concentration of p24 present in the sample determines the signal intensity. The fluorescence signal intensity was then recorded using a spectrophotometer (SpectraMax M5 microplate reader) ( 24 ). The calibration plot for the signal intensity versus the concentration of purified HIV-1 p24 antigen was plotted with the measured data, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ratiometric signal between the carbon dots and FITC was used for signal transduction across a linear range of 0.317-35 μg/dL (Wu et al 2016). The doping of europium into silica NPs has also been reported (Tagaya et al 2011) and has been shown to be capable of facilitating HIV p24 antigen detection in clinical samples (Chunduri et al 2017).…”
Section: Immunoassays and Biosensorsmentioning
confidence: 99%